Research on Safety Management Application of Dangerous Sources in Engineering Construction Based on BIM Technology. (11th December 2019) - Deng, Langni; Zhong, Mengjun; Liao, Ling; Peng, Lai; Lai, Shijin
Abstract : The construction industry is a high-risk industry, so many scholars have done research on how to reduce safety accidents at the construction site. However, due to the existence of hidden dangers in construction, accidents at the construction site still plague the development of the construction industry. Therefore, effective management of construction hazards is an important step to strengthen construction safety. At present, the technology of BIM has been gradually applied to various fields of construction projects, providing strong support for the smooth development of construction projects. Therefore, the purpose of this paper is to create a construction hazard source safety management module through secondary development of the Revit platform. At the same time, the Navisworks software is used to simulate the emergency rescue of construction safety accidents and formulate the corresponding emergency management plan. Finally, an engineering example is used to verify the performance of the development management module. The results show that (1) the security management module created in this paper is highly operational, easy to use, and real-time data update, which has important guiding significance for actual construction safety management; (2) simulation of construction safety accidents through Navisworks software can provide emergency management plans for engineering projects.